Blanking period antiarrhythmic drugs after catheter ablation for atrial fibrillation: a meta-analysis of randomized controlled trials - Chen, Gang; Li, Guangling; Zhang, Demei; Wang, Xiaomei; Guo, Xueya (Frontiers in Cardiovascular Medicine, 2023)
Background Antiarrhythmic drugs (AADs) are frequently prescribed following catheter ablation (CA) for atrial fibrillation (AF). However, to date, there is a lack of large-scale, multicenter controlled studies that have confirmed the efficacy of AADs in reducing the incidence of late recurrence of AF after CA. Furthermore, the optimal duration of short-term use of AADs after CA remains a controversial topic. Methods PubMed, Embase, Cochrane Library, CNKI, and ClinicalTrials.gov were searched until April 25, 2022. We conducted a meta-analysis of randomized controlled trials (RCTs) to assess the efficacy of blanking period AADs in predicting both early and late recurrence of AF. In addition, Grading of Recommendations Assessment, Development and Evaluation (GRADE) was used to assess the quality of evidence in this meta-analysis. Results 12 RCTs with 3,625 patients were included in this meta-analysis. Short-term use of AADs after AF ablation reduced the risk of early recurrence of AF compared with the no-AADs group. In the subgroup analysis of AADs use time, it was found that only using AADs for more than 2 months can reduce the early recurrence of AF after CA. However, when compared with the no-AADs group, short-term use of AADs after CA did not reduce the incidence of late recurrence of AF. Conclusions Short-term use of AADs (more than 2 months) can reduce the early recurrence but not the late recurrence of AF after CA.